EVALUASI TUTUPAN LAHAN PASCA PENETAPAN KAWASAN TAMAN BURU MASIGIT KAREUMBI (TBMK) BERBASIS SISTEM INFORMASI GEOGRAFIS - Luth, Fahriza; Susila, Rian; Fahmi, Raizal; Pasecha, Kilana (Fakultas Kehutanan Universitas Winaya Mukti, 2022)
Masigit Kareumbi Game Park (Taman Buru Masigit Kareumbi or TBMK) is a conservation forest that can be used to accomodate game tourism with 12.42070 ha area. In 1998, PT. Prima Multi Sarana (PMS) was given permission to conduct pine resin extraction in 2005 in TBMK area of PT. PMS; however they disobeyed the code of conduct by taking away the wood forest products (Hasil Hutan Kayu or HHK) causing forest damage that leading to the change of land cover in TBMK area. The purpose of this research is to find out how much change of land cover in TBMK after the game park establishment, and the factors that affect the change. This study used spatial data method with SIG system andÂ Snowball Sampling technique in getting respondentsâ€™ samples. The result showed that TBMK in Cimanggung Adminiatrative Area had 468,66 ha land cover change in each closing type area from 1997 to 2017. The factors that cause the change of land cover in TBMK are the misuse of permission by PT. PMS, farmers activities in the area, unsettled area border, the lack of area guard and the socialization for the villagers, and the weakness of law enforcement